A pharmacologic target of G3139 in melanoma cells may be the mitochondrial VDAC - Lai, Johnathan C. (National Academy of Sciences, 2006)
G3139, an 18-mer phosphorothioate antisense oligonucleotide targeted to the initiation codon region of the Bcl-2 mRNA, can induce caspase-dependent apoptosis via the intrinsic mitochondrial pathway in 518A2 and other melanoma cells. G3139-mediated apoptosis appears to be independent of its ability to down-regulate the expression of Bcl-2 protein, because the release of mitochondrial cytochrome c precedes in time the down-regulation of Bcl-2 protein expression. In this study, we demonstrate the ability of G3139 and other phosphorothioate oligonucleotides to bind directly to mitochondria isolated from 518A2 cells. Furthermore, we show that this interaction leads to the release of cytochrome c in the absence of a mitochondrial membrane permeability transition. Our data further demonstrate that there is an interaction between G3139 and VDAC, a protein that can facilitate the physiologic exchange of ATP and ADP across the outer mitochondrial membrane. Evidence from the electrophysiologic evaluation of VDAC channels reconstituted into phospholipid membranes demonstrates that G3139 is capable of producing greatly diminished channel conductance, indicating a closed state of the VDAC. This effect is oligomer length-dependent, and the ability of phosphorothioate homopolymers of thymidine of variable lengths to cause the release of cytochrome c from isolated mitochondria of 518A2 melanoma cells can be correlated with their ability to interact with VDAC. Because it has been suggested that the closure of VDAC leads to the opening of another outer mitochondrial membrane channel through which cytochrome c can transit, thus initiating apoptosis, it appears that VDAC may be an important pharmacologic target of G3139.